ENGLISH LEARNING PROGRAM FOR CHILDREN IN ORPHANAGE, MUARA ANGKE, NORTH JAKARTA - Recard, Michael Recard; Ani, Yubali; Cendana, Wiputra; Agustin, Atalya; Indriani, Siane; Sativa, Riza (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
To provide quality and equitable education (SDG4), starting from one small area in Jakarta, a community service English Program was held by the Sunda Kelapa Sector Police, North Jakarta and UPH lecturers to teach English to elementary school children at the Orphanage in Muara Angke, Tanjung Priok, North Jakarta. This program was assisted by tutors from students of the Faculty of Education, Pelita Harapan University, while the lecturers supervise the planning and teaching process. This activity aims to train children's communication skills using English. As an international language, English is chosen to be taught to children. Holistic and collaborative technological innovation is used to understand the social and cultural context. Storytelling, conversation, coloring, naming, pronunciation, roleplay, and gamification are used in the learning method. The results of the service show reading and writing skills, increased learning motivation, introduction to material that still needs to be improved, training tutors' teaching skills in guiding and knowing the material properly, and teaching equipment that needs to be improved. In addition, from the learning experience they had, they could learn and play at the same time, feel more confident, and be more active as they increase their sense of competition to achieve the learning goals.